Regulation of dithiafulvene-based molecular shape and aggregation on TiO2 for high efficiency dye-sensitized solar cells. Issue 7 (28th January 2019) - Wu, Yuezhen; Zhang, Quande; Li, Jie; Tian, Xia; Li, Da; Lu, Xiaoqing; Xu, Bingshe; Wu, Yucheng; Guo, Kunpeng
Abstract : Dithiafulvene-based sensitizers with different flare angles need to undergo different types of dye aggregation to maximize the performance of dye-sensitized solar cells. Abstract : A well-matched relationship between the molecular shape and aggregation of donor–π–acceptor (D–π–A) organic dyes is of great significance for realizing the principle of maximizing the performance of dye-sensitized solar cells (DSCs). To this end, two dithiafulvene-based organic sensitizers with different molecular shapes were synthesized, and the influence of their aggregation on TiO2 on the various performance parameters of DSCs was investigated. It was found that V-shapedDTF-C5, with a larger flare angle of 150.6° between the donor and acceptor units in the molecular structure, tended to form compact aggregates on the surface of TiO2 without the loss of adsorbed dyes, thus giving a higher short-circuit density ( J sc ) of 14.92 mA cm −2 and a power conversion efficiency (PCE) of 7.39%; these values were 1.48 and 1.53 times higher than those of a DSC with a CDCA co-adsorbent, respectively. On the other hand, DTF-C6, possessing a typical V-shaped conformation with a flare angle of 120.6°, needed to co-adsorb with CDCA to fill the vacant sites between the dye aggregates on the TiO2 surface, with the aim of reducing current loss and suppressing electron recombination. Compared to a DSC with pristineDTF-C6 aggregation, an example based on the co-adsorbed system dramatically raised the PCE from 5.50% to 9.04%, owing to the improved J sc and open-circuit voltage values. This work presents a perspective for the rational regulation of molecular shapes and the dye aggregation of organic dyes for highly efficient DSCs.